THE DEVELOPMENT OF UZBEK AND WORLD LITERARY CRITICISM - Yomgʼirova Durdona Begzod qizi; Nurmuxammadova Dilshoda (World Scientific Research Journal, 2025)
Abstract: This article analyzes the development of Uzbek and world literary criticism, tracing its evolution from the early 20th century to the present day. It investigates the various historical, political, and cultural forces that have shaped the development of literary studies in Uzbekistan and globally. The paper emphasizes the emergence of influential literary movements such as postcolonialism, structuralism, and cultural studies, and their impact on the shaping of literary criticism in both national and international contexts. The study also underscores the increasing integration of Uzbek literary criticism into the global academic arena, reflecting how it has adapted to both local and global intellectual shifts. The conclusion highlights the contemporary state of Uzbek literary criticism and its growing influence on the wider academic world.